The relevance of PTEN-AKT in relation to NOTCH1-directed treatment strategies in T-cell acute lymphoblastic leukemia - Rui D. Mendes; Kirsten Canté-Barrett; Rob Pieters; Jules P.P. Meijerink (Haematologica, 2016)
The tumor suppressor phosphatase and tensin homolog (PTEN) negatively regulates phosphatidylinositol 3-kinase (PI3K)-AKT signaling and is often inactivated by mutations (including deletions) in a variety of cancer types, including T-cell acute lymphoblastic leukemia. Here we review mutation-associated mechanisms that inactivate PTEN together with other molecular mechanisms that activate AKT and contribute to T-cell leukemogenesis. In addition, we discuss how Pten mutations in mouse models affect the efficacy of gamma-secretase inhibitors to block NOTCH1 signaling through activation of AKT. Based on these models and on observations in primary diagnostic samples from patients with T-cell acute lymphoblastic leukemia, we speculate that PTEN-deficient cells employ an intrinsic homeostatic mechanism in which PI3K-AKT signaling is dampened over time. As a result of this reduced PI3K-AKT signaling, the level of AKT activation may be insufficient to compensate for NOTCH1 inhibition, resulting in responsiveness to gamma-secretase inhibitors. On the other hand, de novo acquired PTEN-inactivating events in NOTCH1-dependent leukemia could result in temporary, strong activation of PI3K-AKT signaling, increased glycolysis and glutaminolysis, and consequently gamma-secretase inhibitor resistance. Due to the central role of PTEN-AKT signaling and in the resistance to NOTCH1 inhibition, AKT inhibitors may be a promising addition to current treatment protocols for T-cell acute lymphoblastic leukemia.